ANALISIS STRATEGI KOMUNIKASI KRISIS HUMASDA PT. KERETA API INDONESIA (PERSERO) DAERAH OPERASIONAL 2 BANDUNG (Studi Deskriptif Dalam Kasus Penertiban Lahan Stasiun Barat)” - Adzkia Arif; Ayub Ilfandy Imran (Alfuad: Jurnal Sosial Keagamaan, 2018)
The research is titled “Analyses of Crisis Communication Strategy of Humasda PT. Kereta Api Indonesia (PERSERO) Operation Area 2 Bandung (Descriptive Study in Case of  Evacuation Land in West Station)”, as for the problem are the concept of crisis processing, the crisis communication strategy, the effort in cope with crisis, PR role when the crisis held by Humasda PT. Kereta Api Indonesia (Persero) Operational Area (Daop) 2 Bandung in solve the crisis that caused by evacuation land in west station. This research used case study qualitative research method of case study along with descriptive exposure. The data obtained through observation, interview, and documents. The main informant in this research is Staff of Humasda Expert PT. KAI Daop 2 Bandung, with the support informant are college student activist, and Kebon Jeruk citizen. Result of this research is crisis communication strategy held by Humasda PT. Kereta Api Indonesia (Persero) Operational Area 2 Bandung already implemented, start from the existence of strategy in cope with crisis, existence of crisis center, and strategy of good media communication. However, the weakness of crisis communication strategy implementation by Humasda PT. Kereta Api Indonesia (Persero) Operational Area 2 Bandung is not doing any direct communication event to the society who give a gap for a developing more crisis.